Bioactivity of venom extracted from the sea anemone Anthopleura asiatica (Cnidaria: Anthozoa): Toxicity and Histopathological studies - Ramkumar S.,Venkateshvaran K.1; Arun Sudhagar S (Advances in Aquaculture and Fisheries Management, 2020)
The bioactivity of the venom from a locally available sea anemone, Anthopleura asiatica collected from the Mumbai coast was studied. The crude venom from sixty sea anemones (Sixty numbers) was extracted in aqueous medium. The protein content of the crude venom was 4.3459±0.027 mg/ml. The crude venom was found to be lethal at 1ml when injected intra-peritoneal to kasuali strain male albino mice (20±2 g). The crude venom was partially purified by anion exchange chromatography using a step-wise gradient of 0.1-1.0M NaCl and 10 fractions each of 15 ml, F1 – F10 were collected. Fractions F8, F9 and F10 exhibited lethality to mice, upon envenomation. The symptoms of toxicity observed in the mice indicated that the venom affected the central nervous, cardiovascular and urinary systems. Histopathological study revealed accumulation of polymorphic nuclear cells with necrosis in brain, hemolysis in heart, occlusion with hemolysed blood in kidney and necrosis, vacuolation with pleomorphic nuclear material and hemolysis in liver.